Formulation and Evaluation of Floating Alginate Beads of Diclofenac Sodium (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The objective of this present investigation is to develop gastroretentive sustained release alginate beads of Diclofenac sodium by the ionotropic gelation method. The floating beads were prepared by dispersing Diclofenac sodium together with CaCO3 (as gas forming agent) into a solution of sodium alginate. The resulting solution was then extruded through a 22 gauge syringe needle into 100 ml cross-linking solution containing calcium chloride (1% w/v) plus acetic acid (10% v/v). Prepared beads were evaluated for their encapsulation efficiency, buoyancy test, FT-IR spectroscopy, scanning electron microscopy (SEM) and release behaviour. In vivo floating behaviour was studied by sonography. The drug entrapment efficiency was increased with the increment of polymer ratio. All of the formulations (F1 to F5) floated immediately or with a very short lag time and remained floating upto 24 hours. Rough and porous surface was observed in case of surface SEM and many large hollow pores or multiple small hollow pockets were observed in case of cross-sectional SEM of beads. In vivo floating behaviour of the beads was confirmed by ultrasonographic examination of a healthy male volunteer after ingestion of capsule containing floating beads. In vitro dissolution studies were performed for eleven hours into 900 ml 0.1N HCl (pH 1.2) using USP Apparatus II (paddle type) maintained at a temperature of 37ºC and stirred at a speed of 50 rpm. The dissolution study revealed that, after eleven hours the percent of drug release for five formulations were 76.7% (F1), 73.5 % (F2), 72.2 % (F3), 70.56% (F4), and 69.1 % (F5) and all of the formulations followed zero order and Higuchi model. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12484 Dhaka Univ. J. Pharm. Sci. 11(1): 29-35, 2012 (June)